2015
DOI: 10.1590/abd1806-4841.20153736
|View full text |Cite
|
Sign up to set email alerts
|

Nail involvement in adult patients with plaque-type psoriasis: prevalence and clinical features

Abstract: BACKGROUND:Psoriasis is a disease of worldwide distribution with a prevalence of 1 to 3%. Nail psoriasis is estimated in 50% of patients with psoriasis, and in the presence of joint involvement, it can reach 80%.OBJECTIVE:To study the nail changes - and their clinical implications - presented by patients with psoriasis vulgaris under surveillance in a university hospital from the south of Brazil.METHODS:his cross-sectional study evaluated 65 adult patients from January 2012 to March 2013. Cutaneous severity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
(43 reference statements)
0
21
1
5
Order By: Relevance
“…Few studies, also examining only nail psoriasis patients found a substantially higher prevalence of onychomycosis among them; it is possible that the inclusion of patients currently being or having recently been treated with immunosuppressive agents can justify the noted difference . The majority of studies examining psoriasis patients with as well as without psoriatic nail lesions have reported a smaller prevalence of onychomycosis than the one found in our study . This discrepancy is possibly attributed to the fact that psoriasis patients with clinically healthy nails seem to be less susceptible to dermatophyte infections of the nail than the general population.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Few studies, also examining only nail psoriasis patients found a substantially higher prevalence of onychomycosis among them; it is possible that the inclusion of patients currently being or having recently been treated with immunosuppressive agents can justify the noted difference . The majority of studies examining psoriasis patients with as well as without psoriatic nail lesions have reported a smaller prevalence of onychomycosis than the one found in our study . This discrepancy is possibly attributed to the fact that psoriasis patients with clinically healthy nails seem to be less susceptible to dermatophyte infections of the nail than the general population.…”
Section: Discussioncontrasting
confidence: 85%
“…[38][39][40] The majority of studies examining psoriasis patients with as well as without psoriatic nail lesions have reported a smaller prevalence of onychomycosis than the one found in our study. 8,13,[41][42][43][44][45][46][47] This discrepancy is possibly attributed to the fact that psoriasis patients with clinically healthy nails seem to be less susceptible to dermatophyte infections of the nail than the general Case, infection proved through mycological testing; n, natural number; Percentage, refers to the total of infection cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Laborde et al have shown that there is an 80% to 90% lifetime incidence of nail involvement in psoriatic patients [4]. The presence of nail involvement of psoriasis is associated with an increase in patient-reported pain complaints, functional impairment and social burden, resulting in a significant restriction of daily activities and quality of life as well as resistance to treatment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%